Prevalence of diabetic retinopathy in children and adolescents at an urban tertiary eye care center. Issue 5 (31st May 2020) - Porter, Mark; Channa, Roomasa; Wagner, Jessica; Prichett, Laura; Liu, Tin Yan Alvin; Wolf, Risa M.
Abstract: Background: Diabetic retinopathy (DR) is a serious complication that can progress to sight‐threatening disease. The prevalence of DR in youth with diabetes has been reported to be 3.8% to 20%. Objective: We aimed to evaluate the prevalence of DR among youth with diabetes at a large ophthalmologic referral center. Secondary goals were to determine the risk factors for DR and severity of disease. Methods: Retrospective chart review of 343 patients with diabetes, <21 years of age, seen at a tertiary referral eye care center from 2013 to 2018. Results: The study included 343 patients, of which 293 had type 1 diabetes (T1D) and 50 had type 2 diabetes (T2D). Thirteen of 343 patients had DR, with an overall incidence of 3.8% (3.4% in T1D and 6% T2D). DR severity included nine with mild non‐proliferative, three moderate non‐proliferative, and one with proliferative DR. Patients with hemoglobin A1c (HbA1c) > 8% had a higher risk of DR ( P = .049). In this cohort, none of the patients with an HbA1c <8% had DR. In the multivariate analysis, a higher systolic blood pressure was marginally associated with risk for DR ( P = .07). Conclusions: We found lower prevalence of DR in youth with diabetes than previously reported. The incidence of DR was higher among patients with T2D and occurred with a shorter duration of disease, as compared with T1D. While the incidence of DR in youth with T1D is low, with the increasing incidence of T2D in adolescents and early risk for DR, early screening must be emphasized.